Tinjauan Yurdis terhadap Dampak Keterlambatan Pendaftaran Akta Kelahiran bagi Anak - Anak Agung Putra Agung Dwicahyana; Anak Agung Sagung Laksmi Dewi; Anak Agung Istri Agung (Jurnal Interpretasi Hukum, 2022)
A birth certificate is a piece of paper issued by the civil registry office for the birth of a person as a form of identity for each child. This research is due to the delay in registration of birth certificates in Badung Regency which causes legal consequences for both children and parents. So the purpose of this research is to discuss the mechanism for registering birth certificates for children who are late in registering their births at the Population and Civil Registration Office of Badung Regency and to analyze the legal impact of late registration of birth certificates. The research method used in this research is empirical legal research, based on facts from the results of a field survey which is to examine the applicable legal provisions and how the law applies in society. The sources of legal materials for this research are primary and secondary sources using interview and note-taking techniques in collecting data. This research discusses the importance of birth certificates, the relationship of legal status to children associated with delays in making birth certificates, the mechanism for registering a child's birth certificate late and the legal impact of delays in registering a child's birth certificate. If a child obtains a birth certificate, it is a form of legal protection provided by the state to children, this protection is the rights of everyone, including children, and to be able to obtain an identity and citizenship based on the child's status so that it is legally valid. Birth registration is a basic right of legal recognition of that person's existence.